2008
DOI: 10.1007/s00426-008-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

“Octave illusion” or “Deutsch’s illusion”?

Abstract: The "Deutsch's illusion" occurs in most people when a dichotic pair of tones spaced an octave apart is presented repeatedly in alternation, so that when the right ear receives the high tone, the left ear receives the low tone, and vice versa. The illusory percept consists typically in a single low tone heard at one ear alternating with a single high tone heard at the other ear. Here, we investigate whether the frequency interval between the tones and their duration play a role in the perception of the illusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…1). This phenomenon was first described by Deutsch (1974) and appears to be restricted not only to tones that are separated by an octave but can also to that occur with larger and smaller intervals (Zwicker, 1984;Brancucci et al, 2009). As shown in the lower portion of Fig.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…1). This phenomenon was first described by Deutsch (1974) and appears to be restricted not only to tones that are separated by an octave but can also to that occur with larger and smaller intervals (Zwicker, 1984;Brancucci et al, 2009). As shown in the lower portion of Fig.…”
Section: Introductionmentioning
confidence: 80%
“…Furthermore, the mechanisms of binaural diplacusis and harmonic binaural fusion proposed by Chambers and colleagues can be questioned on the basis of previous research using pure-tone stimuli, which showed that Deutsch's illusion can be elicited by intervals smaller than an octave (Zwicker, 1984;Brancucci et al, 2009). Furthermore, Brancucci and colleagues showed that the salience of Deutsch's illusion decreased with reduced frequency separation between pure tones (Brancucci et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations